Hard work pays off - Fraser, Mat (Athlete); Mestel, Spenser; Moniz, Sammy; Regone, David (London: CENTURY, 2022)
Fittest Man on Earth Mathew Fraser, five-time winner of the CrossFit Games, shares his exercise program as well as insights into his CrossFit competition experiences and strategies.
Introduction -- How to use this guide -- Strength -- Endurance -- Speed -- Coordination -- Mentality -- Recovery -- Acknowledgments -- Additional Mat Fraser workouts -- HWPO workout log -- Glossary.
Keywords: Fraser, Mat -- (Athlete) -- Anecdotes; Exercise; Physical fitness; Nutrition; Exercise; Nutritional Physiological Phenomena; Nutrition; HEALTH & FITNESS / Exercise / General; SPORTS & RECREATION / Training; Exercise; Physical fitness; Cookbook; recipes; Anecdotes; Recipes